The Use of GAC (Granular Activated Carbon) and Zeolite as an Adsorbent to Reduce The Concentration of Phosphate in Laundry Wastewater - Felicia Naila Nasir; Harmin Sulistyaning Titah (Jurnal Syntax Transformation, 2024)
The growth of the laundry business increases every year along with population growth, however the laundry waste produced is generally thrown straight into the drain and flows into water bodies without prior treatment. The threshold limits for laundry wastewater quality standards for phosphate content, Chemical Oxygen Demand (COD) and Total Suspended Solid (TSS) are 10 mg/L respectively based on East Java Governor Regulation No. 72 of 2013. Disposing of laundry waste directly in large quantities into water bodies can have negative effects on the ecosystem in water bodies and water pollution problems. This research aims to determine the efficiency of using GAC and zeolite adsorbents in reducing phosphatelevels in laundry liquid waste. Based on the impact that can pollute water bodies, it is necessary to process laundry liquid waste. One of the processing methods used is the adsorption method, the adsorption process is carried out using Granular Activated Carbon (GAC) and zeolite with a batch system. This research uses liquid wastewater samples from laundry businesses. The variations used in this research are the adsorbent mass, and contact time. The results obtained from this research include SEM (Scanning Electron Microscopes) test results and the percentage reduction in phosphatelevels using GAC and zeolite adsorbents in batch systems. The research results show that the optimum adsorbent mass is 12 grams of adsorbent mixed with GAC and zeolite with a contact time of 150 minutes with a percentage reduction in phosphate levels of 57.14%. The phosphate values of laundry liquid waste after processing with adsorbent mass, adsorbent composition and optimum contact time are 6.5 mg/L.